PEMBINAAN PEGAWAI DALAM PELAKSANAAN TUGAS DI BIRO UMUM KANTOR GUBERNUR PROVINSI SUMATERA SELATAN - Dian Anggraini (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
The goal of this research are to see information about employee coaching duties. The population is 151 employee and the sample is 53 people that taken by stratified proportional random sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score. The result of this research are the employee coacing duties Biro Umum Kantor Gubernur Provinsi South Sumatra. Stay in is Good category.